Análisis geométrico de vacíos cósmicos para la acotación de parámetros cosmológicos (2020)
Cosmic voids, regions of tens of Megaparsecs with a density of matter less than the cosmological average, are a study laboratory for observational cosmology. The morphology and evolution of these voids is influenced by the matter-energy content of the Universe. Recent analytical studies have suggested that it is possible to use the geometric characterization of voids as a test to determine cosmological parameters. In this work, we use large-scale simulations of the dark matter distribution to validate this hypothesis.